Komunikasi Lintas Budaya antara Etnik Samawa dan Sasak dalam Kehidupan Sehari-hari di Dusun Sampar Gilar - Zaini, Hari; Iman, Topan Rahmatul (YASIN, 2024)
Cross-cultural communication is communication carried out as a result of the communication process between various cultural elements. The communication process carried out by two or more cultures. Aims to reduce the level of misunderstanding and minimize the occurrence of conflict. This research aims to find out how communication is between indigenous people and migrant communities in Sampar Gilar Hamlet, Sepakat Village and to find out what are the barriers to cross-cultural communication between the Samawa Ethnic and Sasak Ethnic groups in Sampar Gilar Hamlet. This research uses a qualitative descriptive method based on data perspective as well as observation, interview and documentation collection techniques. Analyzed data interactively using data reduction steps, data presentation and drawing conclusions. The results of cross-cultural research on Samawa and Sasak ethnic groups in Sampar Gilar hamlet using 1) Communication through events (Tradition) 2) Communication through events (Gotong Royong) 3) Communication through (daily activities) and barriers to the cross-cultural communication process of the Sumbawa ethnic group And the Sasak ethnicity in Sampar Gilar hamlet is the difference in language and the meaning of their respective languages, both the Sasak tribe and each Sumbawa tribe.